Role of the Bromide on the Hydrodebenzylation of 2, 4, 6, 8, 10, 12‐Hexabenzyl‐2, 4, 6, 8, 10, 12‐hexaazaisowurtzitane (HBIW). Issue 13 (4th April 2022) - Liu, Wei; She, Chong Chong; Chao, Hui; Wang, Na; Chen, Shu Sen; Jin, Shao Hua; Wang, Jun Feng; Chen, Kun
Abstract: The catalytic hydrogenolysis of 2, 4, 6, 8, 10, 12‐hexabenzyl‐2, 4, 6, 8, 10, 12‐hexaazaisowurtzitane (HBIW) over Pd‐based catalysts in the ternary solvents of acetic anhydride, bromobenzene (PhBr) and N, N'‐dimethylformamide (DMF) was the key step for producing 2, 4, 6, 8, 10, 12‐hexanitro‐2, 4, 6, 8, 10, 12‐hexaazaisowurtzitane (HNIW or CL‐20). However, the role of the bromobenzene is still allusive. Herein, Pd/graphite carbon nitride nanosheets (g‐C3 N4 NS) was used in the hydrogenolysis of HBIW under the atmospheric pressure, and exhibited a yield of 80 % as well as a faster debenzylation rate than Pd/C. By the virtue of the kinetic study, the effect of the bromide, solvent and proton on the debenzylation rate was investigated and discussed. The bromide worked as a co‐catalyst to promote the desorption of the product of the hydrogenolysis from the surface of the palladium nanoparticle. The observation benefits for elucidating the reaction mechanism and may inspire the design of the novel catalysts for the hydrogenolysis of HBIW. Abstract : Pd/g‐C3 N4 NS was successfully prepared by combining the acid exfoliation and chemical reduction methods. The hydrogenolysis of the HBIW showed a fast debenzylation rate when catalyzed over Pd/g‐C3 N4 NS than the Pd/C at 25°C, which is favorite for improving the yield of the reaction. By the virtue of the kinetic study, the bromide acted as the co‐catalyst to promote the desorption of the product of the debenzylation from the surface of the palladium surface.